Determining Factors Influencing Purchase Interest in Bank Mandiri Property Collateral through Auction Mechanism - Wahsundari, Emmie (PT FORMOSA CENDEKIA GLOBAL, 2024)
The main objective of national development is to improve the quality of life of the community as a whole. National development has so far been directed to create a just and prosperous society based on the principles of Pancasila and the 1945 Constitution. The purpose of this study is to identify the elements that influence the desire to obtain collateral at Bank Mandiri through an auction procedure. This study was conducted as a field study using quantitative methodology, using a questionnaire for data collection. Purchase intention serves as the dependent variable, while three independent variables, namely price, location, and promotion, were studied. Furthermore, this study included intervening variables related to culture. The sample consisted of 100 respondents, selected through a proportional random sampling technique. The collected data were then examined through descriptive statistics and the Partial Least Square (PLS) method, utilizing SmartPLS version 3 software for analysis.